Analysis of NB-IoT technology character and networking - Guang-hui ZHANG; Zhen-qiang SUN; Na LU (物联网学报)
In order to meet cellular Internet of Things development requirements,3GPP R13 released NB-IoT,which had characters of wide area coverage ,large connections,low power,low cost and low rate.Technology theory and character of NB-IoT were firstly introduced,then NB-IoT network scheme,industry status and development prospect were analyzed.At last,NB-IoT ecosystem and services were summarized.